Contraceptive use Transition and Fertility Dynamics and Reproductive Health Outcomes in Zambia - Phiri, Million (University of the Witwatersrand, Johannesburg, 2024)
Background: Improving access to and utilisation of contraceptive methods has been a major global goal of maternal health and development programming for over four decades now. Despite the benefits associated with contraceptive use, the prevalence in Zambia is still low. The country’s population policy has identified high fertility rate, population growth rate and maternal mortality rate as hindrances to the country’s socio-economic development agenda. Although the contraceptive prevalence rate in Zambia is still low, it has been increasing steadily from 15.2% in 1992 to 34.2% in 2001 and then from 40.8% in 2007 to 49.0% in 2018 among women of reproductive age. The sources of the observed increase in the contraceptive rate use were not known. This is because previous studies in Zambia concentrated on examining factors associated with using contraception use rather changes in usage. This study achieved the four specific objectives: (i) describe how contraceptive use has changed in Zambia over time regarding levels and trends; (ii) explore the geographic, social, economic, environmental and demographic factors that explain contraceptive use transition in Zambia; (iii) examine how contraceptive use transitions have affected fertility dynamics (iv) examine how contraceptive use transition has affected reproductive health outcomes in Zambia. Theoretical framework: The theoretical framework used in this study reflects the fact that a woman’s choice to use contraceptive is affected by a complex interplay of social, economic and interpersonal relationships at household or neighborhoods levels. It is in this regard that this study adopted the empowerment and social capital theories, reflecting social phenomena which operate at different level to influence contraceptive use. As such, contraceptive use can be viewed as a function of the level of empowerment among women, their access to social capital, and the degree to which gender inequality and problematic social norms are present in their social environment. The key woman empowerment elements include participation in the decision- making process, education attainment, access and ownership of resources, access to information, employment opportunity, and higher socioeconomic status. Methodology: This study employed a mixed methods research design to examine factors explaining contraceptive use transition in Zambia. Quantitative analysis used a pooled dataset comprising a sample of 44,762 fecund sexually active and non-pregnant women aged (15-49 years) captured in the demographic and health surveys (DHSs) conducted between 1992 and 2018. The DHS is a cross-sectional study which applies a two-stage stratified cluster sampling design to select Enumeration areas and households. Furthermore, qualitative data analysis was conducted on the data collected through focus groups (FGD) with women of reproductive age (n=4) and key informant interviews with key staff (n=10) from the Ministry of Health and stakeholder organisations implementing family planning programmes in Zambia. All the FGDs and key informant interviews were conducted in Lusaka and Chongwe districts. The first objective was achieved by conducting descriptive and trend analysis on data to examine the changes in contraceptive use overtime. Qualitative data was used to explain the reasons behind the observed changes in contraceptive use transition. Analysis for the second was done in two steps. The outcome variable for this study is current contraceptive use. All sexually active women in the DHS were asked a question “Are you currently using any contraceptive method to prevent a pregnancy”. The first step involved application of multilevel regression analysis to examine the influence of both individual and community factors on current contraceptive use in Zambia. The second step involved utilisation of multivariable nonlinear decomposition technique (Blinder Oaxaca decomposition techniques) to measure the contribution effects of both individual and contextual factors to the observed changes in contraceptive use in Zambia. This was also complimented by qualitative data to explain to ii | P a g e explain quantitative results. Objective three was achieved through application of multivariable Blinder- Oaxaca decomposition regression techniques to examine the effects of contraception use changes over time on fertility rate and maternal health outcomes in Zambia. Using a multivariable decomposition regression analysis technique is an improvement over previous similar research works that have been conducted in Zambia. All DHS analysis took into account the complex survey design and statistical significance was determined at α0.05. Key findings: Study findings show that in Zambia's contraceptive prevalence rate rose 30.8 percentage points (14.2% to 45.0%) throughout the analysis period, 1992 to 2018. This translates to an average of 1.2% annually. The major share of contraceptive use increase in Zambia happened between 1992 and 2001 (16.7%). The least change was during 2013 and 2018 (0.2%). Findings show that the rate of increase in CPR has been declining over time, even though overall CPR has increased during the analysis period. The findings show that overall, contraceptive use among sexually active women has increased significantly in Zambia, despite regional, residential, and socioeconomic differences. The study's findings support the proposed research hypothesis that contraceptive use has increased significantly in Zambia. Overall, both changes in women’s compositional structure and changes in women's contraceptive behaviour significantly contributed to the change in contraceptive use in Zambia. Multivariable decomposition analysis of the determinants of change in contraceptive use has revealed that between 1992 and 2018: increase in proportion of women with secondary education (5.20%), reduction experience of child mortality (7.70%), reduction in the proportion of women desiring 6 or more children (5.63%) and increase in proportion of woman decision with making autonomy (3.33%) were the major contributors to the trend change in contraceptive use among sexually active women in Zambia. Results from the decomposition analysis reveal that the observed increase in contraceptive use in Zambia has significantly affected reduction and fertility rate and teenage pregnancy. The study results confirm the hypothesis that the increase in contraceptive use has contributed to the reduction in fertility rate and teenage pregnancy. Conclusion: Contraceptive utilisation among sexually active women in Zambia has shown a steady and significant progressive increase of 30.8 percentages over the 26-year period from 1992 to 2018. The larger increase in contraceptive use happened during the period 1992-2001. Although there are still regional and area disadvantage in contraceptive prevalence rate, the gap in utilisation between urban and rural areas has narrowed. Women’s compositional factors have contributed differently to contraceptive use increase observed in the country. The observed increase in contraceptive use in Zambia is largely due to changes in the contraceptive behaviour of sexually active women. Positive change in women’s contraceptive behaviour could be attributed to the country’s huge investment in family planning programming by government and stakeholders. However, improvement in women compositional factors, such as education, decision-making autonomy, access to family planning information and child mortality experience reduction among other individual and community-level factors were key in driving contraceptive use transition. Therefore, as emphasized in the empowerment and social capital theories, social change among women is key in influencing contraceptive use transition. Furthermore, the study has established that the noted increase in contraceptive use in Zambia has positively contributed to fertility rate decline. iii | P a g e Implications of results The findings of this current study imply that both changes in women’s social factors and changes in the contraceptive use behaviour of sexually active women in Zambia have been driving contraceptive use transition in Zambia. This signifies that the investments in family planning programmes have been yield expected results by changing contraceptive behavior of women. The study findings further suggest that understanding social context is key to inform the design of new FP strategies and strengthening of exiting interventions aimed at further improving acceptance and utilisation of contraceptive methods among women. Contribution to knowledge of the study The study has made a contribution to research by delineating social factors that have contributed to the observed contraceptive use transition in Zambia. Such findings have not been explored before in the context of family planning research in Zambian. Furthermore, the study has provided evidence of how the observed increase in contraception use in the country has affected fertility, teenage pregnancy rates, and prevalence of unintended births. This information is relevant for understanding the country’s population and maternal health dynamics. The findings not only validate the relevance of core principles of the empowerment and social capital theories in explaining contraceptive use transition in Zambia, but also shed light on other theoretical aspects that should be considered when understanding contraceptive use transition. Future research Future studies should examine rural-urban and regional variations of the determinants of contraceptive use transition. This will generate information to inform regional specific interventions. More so future studies should examine the factors that may influence a person's decision to utilise contraception in the future among sexually active adolescent girls. Doing so will generate data to inform the design of future family planning programmes that appeal to specific target groups. Furthermore, an in-depth qualitative research is required to understand how to overcome barriers of contraceptive use behaviour relating gender norms, cultural beliefs and religious values.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy in Demography and Population Studies, In the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Women of reproductive age; contraception use; reproductive health; fertility control; social context; decomposition analysis; Zambi; SDG-3: Good health and well-being; SDG-5: Gender equality